Analisis Risiko Pada Area Rotary Kiln di PT Gresik Mitra Teknik Guna Pencegahan Kecelakaan Kerja - Reynaldi Ahmad Faizin; Moch. Nuruddin (Fakultas Teknik, 2022)
PT. Gresik Mitra Teknik (PT GMT) is a company in the field of contractor services and trading services. In its operational activities, PT. GMT is inevitable from accidents at work. As the K3 team at PT. GMT, in particular, has recorded cases of work accidents that occur specifically in the area of rotary kilns. Based on data on the number of accidents that occurred in several activities at PT GMT, it was concluded that fire brick installation activities dominated the occurrence of accidents in the company. The purpose of this study is to apply the HIRARC method to identify existing occupational accident risks and identify the steps that need to be taken to manage all existing risks. The results of the study found that there were 10 risks with the following details 2 risks including the low level category, 4 risks including the medium level category, 2 risks including the high level category and 2 risks including the very high level category. Risk control measures focus on reducing the level of risk, which is the highest risk category. The measures taken include the new design of the production floor, the provision of PPE earplugs, regular testing of noise levels.